2018
DOI: 10.1038/s41592-018-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of DNA-immunoprecipitation-based genomic profiling

Abstract: DNA immunoprecipitation followed by sequencing (DIP-seq) is a common enrichment method for profiling DNA modifications in mammalian genomes. However, the results of independent DIP-seq studies often show considerable variation between profiles of the same genome and between profiles obtained by alternative methods. Here we show that these differences are primarily due to the intrinsic affinity of IgG for short unmodified DNA repeats. This pervasive experimental error accounts for 50-99% of regions identified a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 59 publications
5
68
0
5
Order By: Relevance
“…Next, we extended this analysis to 16 distinct 6mdA DIP-seq samples across four independent studies (6,7,9,19), revealing that most of the enriched peaks in all studies were located in repetitive elements overrepresented in both low complexity regions and simple repeats compared to other genomic fractions (52.7-and 27.7-fold, respectively) ( fig. S2, A and B), consistent with off-target binding (20). Although studies have suggested localization of 6mdA to long inter-spersed nuclear elements (LINEs) in mammals (7,8,21), our analysis showed highly inconsistent enrichment of 6mdA DIP-seq over LINEs between samples and studies (−8.9-to 3.6-fold over genomic) ( fig.…”
Section: Artifactual Detection Of 6mda By Anti-6mda Antibodiessupporting
confidence: 80%
See 2 more Smart Citations
“…Next, we extended this analysis to 16 distinct 6mdA DIP-seq samples across four independent studies (6,7,9,19), revealing that most of the enriched peaks in all studies were located in repetitive elements overrepresented in both low complexity regions and simple repeats compared to other genomic fractions (52.7-and 27.7-fold, respectively) ( fig. S2, A and B), consistent with off-target binding (20). Although studies have suggested localization of 6mdA to long inter-spersed nuclear elements (LINEs) in mammals (7,8,21), our analysis showed highly inconsistent enrichment of 6mdA DIP-seq over LINEs between samples and studies (−8.9-to 3.6-fold over genomic) ( fig.…”
Section: Artifactual Detection Of 6mda By Anti-6mda Antibodiessupporting
confidence: 80%
“…Artifactual mapping of 6mdA by DNA immunoprecipitation sequencing 6mdA antibodies are also used in DNA immunoprecipitation sequencing (DIP-seq) to generate genome-wide profiles of 6mdA (8)(9)(10)19). We recently reported major technical errors related to off-target binding of antibodies to DNA repeats in DIP-seq resulting in almost exclusively false-positive signals for 6mdA in vertebrate species Xenopus laevis, Danio rerio, and Mus musculus (20). Comparing published human 6mdA DIP-seq data (7) for paired genomic and WGA DNA revealed highly similar profiles with over 70% of natively enriched 6mdA peaks also found in the WGA sample ( Fig.…”
Section: Artifactual Detection Of 6mda By Anti-6mda Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, cfMeDIP-seq 37 was used to detect and classify adult cancers in an early stage. However, as this method is based on immunoprecipitation it has its own drawbacks 38 . These techniques all cover different parts of the methylome, and the optimal technique for sensitive tumor detection remains yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…According to the team, between 50% and 99% of enriched regions in DIP-seq data might be false positives. They found nonspecific enrichment of areas of the genome called short tandem repeats (STRs) 4 . Other known sources of bias include the fact that the 5-methylcytosine (5mC) antibody labs mainly use preferentially enriches genomic regions of low CG content and the most frequently used 5-hydroxymethylcytosine (5hmC) antibody does the same at highly modified regions of the genome.…”
Section: Dip-seq Peculiaritiesmentioning
confidence: 99%